Management of external jugular vein aneurysm: a systematic review. (June 2022) - Nana, Petroula; Gkrinia, Eleni; Maiou, Chara; Karyda, Ourania; Korais, Christos; Spanos, Konstantinos; Kouvelos, Georgios
Introduction: Aneurysms of the jugular vein system are rare and high clinical suspicion is needed for diagnosis. External jugular vein aneurysms (EJVA) are considered innocent lesions that need treatment mainly for aesthetic reasons. The aim of this systematic review was to present current literature regarding diagnosis and management of EJVAs. Methods: A literature review was conducted through the Pubmed/Medline and Scopus regarding articles referring on EJVA from 2000 to 2020. Using the PRISMA guidelines (Preferred Reporting Items for Systematic reviews and Meta-Analyses), 30 articles were identified, according to inclusion criteria. Demographics, clinical characteristics, etiology, diagnostic imaging, complications, treatment, and histopathological findings were recorded and analyzed. Results: Twenty-seven case reports and one case series were identified, including 30 patients and 31 EJVAs. One-third of patients (30.3%) were < 18 years old (mean age 32 years, range 1–72 years) and 54% of them were females. In 51% of the cases, the lesion was characterized as a true aneurysm after histological evaluation. The presence of a soft cervical mass was the most common clinical symptom, while Valsalva maneuver pointed out the presence of an EJVA in 66.7% of patients. Diagnosis was achieved using ultrasonography, computed tomography, or magnetic resonance imaging. Forty-three percent of the patients underwent more than one radiological examination. Twenty patients underwent surgical management. The primary indication of surgical treatment was aesthetic reasons (11/20, 55%). Thrombosis was the most common EJVA complication (11/30, 36.3%). Conclusions: Differential diagnosis of neck mass should include EJVA. High clinical suspicion and adequate imaging are important for diagnosis. Open surgical approach is the more commonly applied therapeutic strategy.